Investigation of Bacillus pumilus and Staphylococcus haemolyticus adhesion on 304L Stainless Steel in Atmospheric Simulated Medium - Aabedy, Amal El; Ibnsouda, Saad Koraichi; Farricha, Omar El (European Scientific Journal, ESJ, 2019)
The bacteria adhesion on materials surface is the first step to formation of biofilm that could lead to biocorrosion. This study aimed to investigate the correlation between bacteria adhesion and the physicochemical properties of both materials and bacteria in atmospheric simulated medium. The material used in this study is 304L stainless steel and Bacillus pumilus and Staphylococcus haemolyticus bacteria strains. The hydrophobicity, electron donor and electron receptor properties were determined by contact angle measurements. In addition, the bacteria capacity of adhesion was followed by using a scanning electron microscope. The contact angle measurements finding showed that both bacteria have hydrophilic surfaces qualitatively and qualitatively. Otherwise, the stainless steel has revealed a hydrophobic character qualitatively and quantitatively. Moreover, the scanning electron microscope displayed the high speed of adhesion of the studied bacteria. The contact angle measurements could be used as a mean to prevent biocorrosion caused by bacteria adhesion.